Generalized group chain acceptance sampling plan - Zain, Zakiyah; Mughal, Abdur Razzaque; Aziz, Nazrina (2015)
In this article, we proposed an acceptance sampling plan based on generalized group chain truncated life test.The decision on acceptance of a submitted lot can be made by using the cumulative information of the immediately preceding samples.The design parameters of the proposed plan such as the minimum number of groups are found to satisfy the desired quality standard.The benefits of this plan include smaller sample size and reduced overall costs.